Unearthing The Psycho-Spiritual Values Within The Training Module for Disaster Workers - Khatijah Othman; Nik Nadian Nisa Nik Nazli; Nurhafizah Mohd Sukor; Zulfadhli Hamzah; Nor Adila Syahira Jusoh; Muhammad Khairi Mahyuddin; Mashitah Sulaiman; Suhailiza Md. Hamdani; Yuseri Ahmad; Marina Munira Abdul Mutalib (USIM Press, 2024)
Vol. 23 No. 2 (2020): Journal of Islamic Social Sciences and Humanities (Special Issue)